2013
DOI: 10.6002/ect.2012.0286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Products on Nosocomial Infections in Liver Transplant Recipients

Abstract: Objectives: Infection is the most severe complication after an organ transplant. Blood cell transfusion is an independent risk factor for adverse events, including infection in the recipient. This study sought to evaluate the effect of blood product transfusions on nosocomial infections in liver transplant patients. Materials and Methods: Patients who underwent a liver transplant at our hospital between 2003 and 2010 were recruited for this study. Exclusion criteria were incomplete records, patients who were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
(42 reference statements)
1
12
0
1
Order By: Relevance
“…Of the infected patients, sixteen (55.1%) were associated with pathogens, while the remaining thirteen patients had only clinical signs of infection. 4 These findings corroborate the data from the present study, which presented a 28.3% infection rate among the study participants, and the majority (56.3%) had positive culture results.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Of the infected patients, sixteen (55.1%) were associated with pathogens, while the remaining thirteen patients had only clinical signs of infection. 4 These findings corroborate the data from the present study, which presented a 28.3% infection rate among the study participants, and the majority (56.3%) had positive culture results.…”
supporting
confidence: 82%
“…This fact may be associated with the small number of transfusions in the sample or with autologous transfusion, which is performed during the LT of the hospital institution of this study, through a process of blood collection and reinfusion, with the objective of reducing and, if possible, eliminating the need for allogeneic blood transfusion, reducing the probable infectious and noninfectious complications. 17 Researches carried out with liver receptors have identified that the transfusion of blood products was associated with the development of PO infection, which contributes to increased morbidity and mortality after LT. 4,12,18 The length of stay in the PO was greater among patients who have acquired HCRI in comparison to those who have not acquired it, showing statistically significant association. These findings corroborate the result of another study that points to the prolonged time of hospitalization as a risk factor for the development of HCRI in liver recipients, conducted in a university hospital located in Korea, where 144 patients were assessed.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…[4,5] However, neither intraoperative massive blood loss nor blood product transfusion is without risks. [6,7] Both may adversely affect postoperative outcomes, increase health care costs, and prolong hospitalization. [8] Therefore, identifying factors influencing intraoperative massive blood loss in patients undergoing scoliosis surgery is vital to establish an optimal blood conservation strategy in an era of blood supply shortage.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] In this regard, identifying predictors of MT is an area of continuous research. Considering 1-year graft survival is decreased in recipients receiving more than four units of blood transfusion,[ 13 ] we conducted this retrospective analysis to identify factors which could predict the need for transfusion of more than four PRBCs intraoperatively. Forty-three perioperative factors of patients who underwent LDLT over 5 and half years at a single centre in India were analysed.…”
Section: Discussionmentioning
confidence: 99%